A comparison of modern and historical methods for calculating Montgomery steamfunction. (28th January 2013) - Market, Patrick S.; Rochette, Scott M.; Lupo, Anthony R.
Abstract The suggestion has been made that the Montgomery streamfunction is now calculable for isentropic analysis purposes simply by applying the equation Ψ = gZ + cpT . Historically, this practice has been frowned upon, as measurements aloft did not have the accuracy requisite to allow such practice. Instead, an integral approach to calculating Ψ has been preferred to get workable values. Yet, advancements in the accuracy of radiosonde measurements have occurred, especially with global positioning system (GPS)‐verified height data. Herein, we show that the values from the simple and integral methods of getting Ψ are very similar, and differ by only ∼0.2%. © 2012 Royal Meteorological Society